If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8X + -8 = 6X + -5 + (X + -2) Reorder the terms: -8 + 8X = 6X + -5 + (X + -2) Reorder the terms: -8 + 8X = 6X + -5 + (-2 + X) Remove parenthesis around (-2 + X) -8 + 8X = 6X + -5 + -2 + X Reorder the terms: -8 + 8X = -5 + -2 + 6X + X Combine like terms: -5 + -2 = -7 -8 + 8X = -7 + 6X + X Combine like terms: 6X + X = 7X -8 + 8X = -7 + 7X Solving -8 + 8X = -7 + 7X Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '-7X' to each side of the equation. -8 + 8X + -7X = -7 + 7X + -7X Combine like terms: 8X + -7X = 1X -8 + 1X = -7 + 7X + -7X Combine like terms: 7X + -7X = 0 -8 + 1X = -7 + 0 -8 + 1X = -7 Add '8' to each side of the equation. -8 + 8 + 1X = -7 + 8 Combine like terms: -8 + 8 = 0 0 + 1X = -7 + 8 1X = -7 + 8 Combine like terms: -7 + 8 = 1 1X = 1 Divide each side by '1'. X = 1 Simplifying X = 1
| 3(-2x+3)=x+2 | | 0=x^3+12x^2 | | (2x+11)=(6x-9) | | 2(-4x+4)=-56 | | ((2y)^3(y^4))/(8y)^2 | | p(x)=[x-(1+i)][x-(1-i)](x^2-2)(x+3) | | 3(2x+6)=6x-10 | | 15=-3n+1+10n | | s=3.5+-2.5t | | 5e^4x+3=25 | | Lnx-3=2 | | x+(x-5)+(x+25)=176 | | -2t+8t+5=17 | | 63-9n=12-2n | | 2s+5t=7 | | 106x-1=181 | | 8+1.50s=20 | | 3x+y-375=0 | | -6x-8=4x-98 | | 4(2c-3)-2=-6-8(1-e) | | 4(5x+3)=252 | | -6(h-2)=30 | | 60x=26+8x | | -5(-4x+4)=16 | | 33=x/8 | | k^2+4=6 | | p(x)=[x-(1+i)][x-(1-i)] | | f(19)=-64+36x-12x^2+x^3 | | 15p+9p=72 | | 0.92*5.6= | | 5x+8y=131 | | f(-4)=x^(4)/6-10x |